KAJIAN TENTANG KEKUATAN MEREK - Dewi Shanti Nugrahani (SEGMEN Jurnal Manajemen dan Bisnis, 2006)
This article discusses about the power of brand for the company. By having the strength of brand, the company will obtain the consumers trust that they will always choose and loyal toward this brand. The supporting factor in building the strength of brand is the perception of consumer. Keywords: brand, the power of brand, perception